Militarisation and Privatisation of Outer Space: A Grave Threat to Humanity - Yadav, Prabhu Ray (Nepal Journal of Science and Technology, 2021)
Nations are spending millions of amounts in amassing arms and nuclear weapons on Earth and even in Space. Such a situation is bound to lead humanity to the brink of a catastrophic war on Earth and even in Space. In this context, sensible human beings should oppose all war-mongering activities that could ultimately invite the very extinction of humanity. This paper tries to emphasize the consequences of the misuse of arms and ammunition on Earth and in Space. This paper focuses on spreading the need for co-existence of people worldwide and eschews the thoughts of waging a war that may wipe out the humanity’s face from the Earth.